The Emerging Ethics of Humancentric GPS Tracking and Monitoring - Michael, K.; McNamee, A.; Michael, M. (2006 International Conference on Mobile Business, 2006)
The Global Positioning System (GPS) is increasingly being adopted by private and public enterprise to track and monitor humans for location-based services (LBS). Some of these applications include personal locators for children, the elderly or those suffering from Alzheimer's or memory loss, and the monitoring of parolees for law enforcement, security or personal protection purposes. The continual miniaturization of the GPS chipset means that receivers can take the form of wristwatches, mini mobiles and bracelets, with the ability to pinpoint the longitude and latitude of a subject 24/7/365. This paper employs usability context analyses to draw out the emerging ethical concerns facing current humancentric GPS applications. The outcome of the study is the classification of current state GPS applications into the contexts of control, convenience, and care; and a preliminary ethical framework for considering the viability of GPS location-based services emphasizing privacy, accuracy, property and accessibility.